2013
DOI: 10.4028/www.scientific.net/amr.724-725.572
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Influence with Surface Contamination on Aerodynamic Performance of Dedicated Wind Turbine Airfoil

Abstract: A Numerical simulation on the influence of airfoil surface contamination on the aerodynamic performance of wind turbines was performed. It chose the dedicated wind turbine airfoil as the research object. The k-ω Shear Stress Transmission (SST) turbulence model was selected for CFD calculation. The roughness height which arranged evenly on the airfoil was changed from 0.03mm to 2.0mm to obtain the sensitive roughness. The airfoil was divided into 18 sections for analyzing the effect on the lift & the drag c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Wu et al [133] simulated the impact of the presence of contaminants on the surface of a HAWT airfoil, the FFA-W3-211 airfoil, on their aerodynamic characteristics. The airfoil surface was evenly roughened, with roughness heights ranging from 0.03 mm to 2.0 mm.…”
Section: Dust and Sandmentioning
confidence: 99%
“…Wu et al [133] simulated the impact of the presence of contaminants on the surface of a HAWT airfoil, the FFA-W3-211 airfoil, on their aerodynamic characteristics. The airfoil surface was evenly roughened, with roughness heights ranging from 0.03 mm to 2.0 mm.…”
Section: Dust and Sandmentioning
confidence: 99%
“…Wu et al [134] simulated the impact of the presence of contaminants on the surface of HAWT airfoil, FFA-W3-211 airfoil, on their aerodynamic performance. The airfoil surface was evenly roughened, with roughness heights ranging from 0.03mm to 2.0mm.…”
Section: Dust and Sandmentioning
confidence: 99%
“…Wu, Li, & Li (2013) showed that the performance of a wind turbine airfoil is very sensitive to the roughness height of 0.6…”
Section: Introductionmentioning
confidence: 99%